Automated control system of nitrogen oxydes absorption with added oxygen flow - Puhanovskyi, Oleh (My University, 2022)
The results of the development of the automatic control system for the nitrogen oxide absorption apparatus are presented. The automatic adjustment system is built on the basis of fuzzy logic. The proposed system is intended for use with modernized absorption units. The main functions of the control system are regulation of water and air flow. As a result of the operation of the automated control system, the concentration of nitrogen oxides in the tail gases stabilizes.The flow of air added to the unit is also optimized.
Keywords: nitric acid; nitrogen oxide; process control; absorption